Letter from Franklin Hulings to James Curtis Booth - Hulings, Franklin (1861)
Franklin Hulings discusses his concerns with the political differences between his potential references, "Mr. King, Judge Kelly, and Judge Campbell" and the Mint's Director, Col. Snowden, as Hulings attempts to be reinstated as an employee to the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States